Theoretical references for the Comprenhensive General Medicine specialist - Aldana Zapata, Kirenia; Pérez Pérez, Silvia María (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Introduction: the Comprehensive General Medicine specialist is capable of facing dissimilar national and international scenarios, making him a tutor par excellence, a leading figure in the Cuban health system capable of leading Primary Health Care not only to medical students, but also to other professionals, which allows him to reaffirm that the importance of the tutor of this specialty is due to social responsibility of promoting the training of a comprehensive health professionals. Objective: carry out an analysis of the theoretical foundations of the pedagogical preparation of the tutor of the Comprehensive General Medicine specialty that contributes to the improvement of their profesional performance. Methods: this descriptive research is part of the development of the doctoral theses in Clinical Surgical Biomedical Sciences. A review of 186 national and international literature was carried out, in spanish and english, related to the work of the tutor in the medical sciences, selecting 71 articles. Results: Through the review of the literature, it was possible to study the pedagogical training of the Comprehensive General Medicine tutor and define essential concepts for its understanding. Conclusions: the systematization of the theoretical references exposes regularities in the pedagogical training of the Comprehensive General Medicine tutor which contributes to his profesional performance, being responsible for the residents, making him the main axisfor the training of the comprehensive doctor that is needed in this times.